Evaluation of Green Manure Amendments for the Management of Fusarium Basal Rot (Fusarium oxysporum f.sp. cepae) on Shallot - Assefa Sintayehu; Seid Ahmed; Chemeda Fininsa; P. K. Sakhuja (International Journal of Agronomy)
Shallot (Allium cepa L. var. ascalonicum) is the most traditional vegetable crop in Ethiopia. Shallot is susceptible to a number of diseases that reduce yield and quality, among which fusarium basal rot (FBR) caused by Fusarium oxysporum f.sp. cepae (Foc) is one of the most important yield limiting factors in Ethiopia. The present study was designed to evaluate the effectiveness of Brassica crops for the management of shallot FBR on shallot. The experiments were carried out at Debre Zeit Agricultural Research Center using cabbage (Brassica oleracea), garden cress (Lepidium sativum), Ethiopia mustard (B. carinata), and rapeseed (B. napus). The evaluations were done under in vitro and greenhouse conditions. Under in vitro test condition it was confirmed that extracts of Ethiopian mustard and rapeseed showed higher inhibition on the growth of Foc pathogen compared to control. Data on seedling emergence, plant height, plant stand, disease incidence, severity, cull bulbs, and bulb weight were collected in greenhouse experiment. The green manure amendments of rapeseed and Ethiopian mustard significantly reduced disease incidence by 21% and 30% and disease severity by 23% and 29%, respectively. However the plant emergency was not significantly different among treatments in greenhouse test. These results indicated that Ethiopian mustard and rapeseed crops have potential as green manure for the management of FBR disease of shallot crop.